2019
DOI: 10.1007/s40333-019-0063-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbon economic development in Central Asia based on LMDI decomposition and comparative decoupling analyses

Abstract: Low-carbon economic development is a strategy that is emerging in response to global climate change. Being the third-largest energy base in the world, Central Asia should adopt rational and efficient energy utilization to achieve the sustainable economic development. In this study, the logarithmic mean Divisia index (LMDI) decomposition method was used to explore the influence factors of CO 2 emissions in Central Asia (including Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan and Turkmenistan) during the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Among various IDA methods, LMDI is the preferred one because it can perfectly handle zero value and conduct without residuals ( Ang, 2004 ; Ang and Choi, 1997 ). Scholars have done enormous researches on carbon emission decomposition analysis, which covers a wide area from province ( Wang and Jiang, 2020 ), country ( Jiang et al, 2019 ; Ma et al, 2019 ; Yasmeen et al, 2020 ), region ( Li et al, 2019 ; Li et al, 2020 ), to even globe ( Chang et al, 2019 ). Li and Qin (2019) examined challenges for China to peak carbon emission in 2030 from both historical and future perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among various IDA methods, LMDI is the preferred one because it can perfectly handle zero value and conduct without residuals ( Ang, 2004 ; Ang and Choi, 1997 ). Scholars have done enormous researches on carbon emission decomposition analysis, which covers a wide area from province ( Wang and Jiang, 2020 ), country ( Jiang et al, 2019 ; Ma et al, 2019 ; Yasmeen et al, 2020 ), region ( Li et al, 2019 ; Li et al, 2020 ), to even globe ( Chang et al, 2019 ). Li and Qin (2019) examined challenges for China to peak carbon emission in 2030 from both historical and future perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Etem et al [29] evaluated the decoupling process of Turkey and found that Turkey did not make or had made weak decoupling efforts in most cases, and that the biggest factor that had made decoupling efforts was energy intensity. Li et al [30] also found that energy intensity had made the biggest contribution to decoupling through an analysis of Central Asia. Wang et al [31] studied the status and efforts of urban carbon emission decoupling in different industrial stages in China, and concluded that cities in different industrial stages showed different decoupling states, driving forces and effects.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Engo et al [15] Xie et al [17] Etem et al [29] Li et al [30] Yan et al [32] LMDI and Tapio index Energy structure, energy intensity, economic structure, population economic activity [15,30], transmission and distribution loss [17] electrification [17], carbon intensity [29], fossil fuel intensity [29], conversion efficiency [29], carbon coefficient [32], fossil energy share [32], energy efficiency [32], transport activity [32] Wang et al [16] C-D production function, LMDI and Tapio [26], investment structure [26], investment dependence [26], emission reduction [28], energy saving [28], transport share [28] Shi et al [24] Decoupling index Per capita GDP, energy intensity, per capita carbon Zheng et al [27] LMDI and OECD decoupling model Carbon emission coefficient, population energy structure, industrial structure, energy intensity, economic growth…”
Section: National Level Co 2 Emissionsmentioning
confidence: 99%
“…Studies reveal that energy consumption, carbon emission efficiency and economic development are closely linked [31][32][33][34]. The representative research method to measure the factors affecting carbon emission efficiency includes the Structural Decomposition Analysis (SDA) [23], the Index Decomposition Analysis (IDA) [34,35] and the Logarithmic Mean Divisia index (LMDI) [36][37][38]. LMDI is extensively applied in the studies, and solves the residual error and zero value problems [37].…”
Section: Definitionmentioning
confidence: 99%